Trouble the water [videorecording (DVD)] - Lessin, Tia; Deal, Carl; Roberts, Kimberly Rivers; Roberts, Scott (Zeitgeist Films, 2008)
"This astonishing powerful documentary takes you inside Hurricane Katrina in a way never seen on screen. Incorporating remarkable home footage shot by aspiring rap artist Kimberly Rivers Roberts, trapped with her husband in the 9th ward, directors/producers Tia Lessin and Carl Deal weave this insider's view of Katrina with a devastating portrait of the hurricane's aftermath. Trouble the Water takes audiences on a journey that is by turns heart-stopping, infuriating, inspiring and empowering. It's not only about the tragedy of Hurricane Katrina, but about the underlying issues that remained when the flood waters receded-failing public schools, record high levels of incarceration, poverty, structural racism and lack of government accountability"--Container.